Shear failure of a granite pin traversing a sawcut fault. (October 2018) - McLaskey, Gregory C.; Lockner, David A.
Abstract: Fault heterogeneities such as bumps, bends, and stepovers are commonly observed on natural faults, but are challenging to recreate under controlled laboratory conditions. We study deformation and microseismicity of a 76 mm-diameter Westerly granite cylinder with a sawcut fault with known frictional properties. An idealized asperity is added by emplacing a precision-ground 21 mm-diameter solid granite dowel that crosses the center of the fault at right angles. This intact granite 'pin' provides a strength contrast that resists fault slip. Upon loading to 80 MPa in a triaxial machine, we first observed aM -4 slip event that ruptured the sawcut fault, slipped 40 µm, but was halted by the granite pin. With continued loading, the pin failed in a swarm of thousands ofM -6 toM -8 events known as acoustic emissions (AEs). Once the pin was fractured to a critical point, it permitted complete rupture events (M -3) on the sawcut fault (stick-slip instabilities). Subsequent slip events were preceded by clusters of foreshock-like AEs, all located on the fault plane, and the spatial extent of the foreshock clusters is consistent with our estimate of a critical nucleation dimension h* . We also identified an aseismic zone on the fault plane surrounding the fractured rock pin. A post-mortem analysis of the sample showed a thick gouge layer where the pin intersected the fault, suggesting that dilatancy of this gouge propped open the fault and prevented microseismic events in its vicinity. Recorded microseismicity separates into three categories: slip on the sawcut fault, fracture of the intact rock pin, and off-fault seismicity associated with pin-related rock joints. We found that pin fracture events were exclusively implosive (anticrack) even though the shear process zone was overall dilatant. This shows how aseismic effects can lead to unexpected seismic manifestations of certain faulting processes. Highlights: Our experiment: a sawcut fault interacts with an asperity (a pin) of intact rock. When deformed at 80 MPa, recorded seismic events had magnitudes from −8 to −3. AE focal mechanisms or timing and locations distinguish 3 AE categories. Pin fracture produced a swarm of tiny compaction AEs and left an aseismic imprint. The pin could not be distinguished during subsequent dynamic rupture of the sawcut.